Negative electrode composite material and preparation method thereof, negative electrode plate and secondary battery

By using a negative electrode composite material coated with silicon carbon particles in lithium-ion batteries, secondary particles are formed using the cladding layer and binder of lithium polyacrylate and conductive material, the structural stability and expansion rate of silicon carbon negative electrode materials are solved. Problem, improving the cycle stability and safety of the battery.

CN119252884APending Publication Date: 2025-01-03ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411317635.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The poor structural stability, high expansion rate and low conductivity of silicon carbon anode materials in existing lithium-ion batteries limit the cycle stability and service life of the battery.

Method used

A negative electrode composite material, including a core and a functional cladding layer, consisting of silicon carbon particles, which relieves the expansion and breakage of particles by a coating of lithium polyacrylate and conductive material, and forms a two-dimensional pore with micron-scale pores through a binder. Subparticles, reducing internal resistance.

Benefits of technology

It effectively alleviates the expansion of the void between the secondary particles, avoids particle breakage, improves the circulation stability and safety of the material, reduces the expansion rate and internal resistance of the deposition silicon carbon, and enhances the performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252884A_ABST
    Figure CN119252884A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and particularly relates to a negative electrode composite material and a preparation method thereof, a negative electrode plate and a secondary battery. Wherein the negative electrode composite material comprises an inner core and a functional coating layer coating the outer surface of the inner core, and the inner core comprises silicon carbon particles; all adjacent silicon carbon particles are adhered to form secondary particles; the functional coating layer comprises lithium polyacrylate and a conductive material. Compared with the prior art, the negative electrode composite material provided by the invention can enhance the cycling stability of a silicon-carbon negative electrode material, greatly reduces the expansion rate of sedimentary silicon carbon, reduces the internal resistance of the silicon-carbon material, and improves the use safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a negative electrode composite material and a preparation method thereof, a negative electrode sheet and a secondary battery. Background Art

[0002] With the rapid development of global industrialization, the large-scale use of fuel vehicles has caused serious air pollution problems. In particular, the exhaust emissions from fuel vehicles have not only exacerbated the deterioration of urban air quality, but also posed a major threat to human health. Therefore, governments and environmental protection organizations have begun to focus on environmental pollution control and actively promote the use of green energy and new energy vehicles to reduce dependence on fossil fuels and pollutant emissions.

[0003] In the field of new energy vehicles, lithium-ion batteries have become the mainstream power source for electric vehicles due to their high energy density, low self-discharge rate, and high charging efficiency. However, current lithium-ion battery technology still faces challenges such as long charging time and limited driving range, which to some extent restricts the popularity and development of electric vehicles. Therefore, the development of a new battery material that can charge quickly and provide long driving range is crucial to promoting the development of the electric vehicle industry.

[0004] Both graphite and silicon can be used as one of the most commonly used negative electrode materials in lithium-ion batteries. The improvement of the energy density of negative electrode materials has been a research hotspot in the field of scientific research in recent years. However, silicon materials face many problems in practical applications: 1) First, during the lithium insertion process, lithium-silicon alloys expand and break particles due to material expansion, and lithium-silicon alloys react with electrolytes to form a large number of byproducts, which will seriously affect the cycle stability and service life of the battery; 2) Secondly, the existing deposited silicon-carbon negative electrode materials have poor ion conductivity due to the poor intrinsic electronic conductivity of silicon and the multiple interfaces encountered by lithium ions during the conduction process of porous carbon-silicon-porous carbon interfaces; 3) Furthermore, some existing negative electrode materials use polymers, inorganic substances, etc. coated on the outside of silicon materials to inhibit expansion, but the inhibitory effect on expansion is not good. In addition, the current material-side treatment methods for reducing the material expansion rate are generally concentrated on the process, specifically reducing the synthesis of silicon carbide and enhancing the uniformity of silicon deposition; but the process is difficult and the degree of reduction is limited. Therefore, improving expansion from the perspective of structural design is a novel and more promising way. In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention

[0005] The purpose of the present invention is to provide a negative electrode composite material to solve the problems of poor structural stability, high expansion rate and low conductivity of the existing silicon-carbon negative electrode material in view of the shortcomings of the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A negative electrode composite material comprises a core and a functional coating layer coated on the outer surface of the core, wherein the core comprises silicon-carbon particles; all adjacent silicon-carbon particles adhere to each other to form secondary particles; and the functional coating layer comprises lithium polyacrylate and a conductive material.

[0008] Preferably, the conductive material is at least one of carbon nanotubes, carbon nanofibers, graphene, and conductive polymers.

[0009] Preferably, the inner core further comprises a binder, and the silicon-carbon particles are connected by the binder to form secondary particles having pores of micrometer level or above.

[0010] Preferably, the particle size DV50 of the secondary particles is 11-15 μm.

[0011] Preferably, the binder is asphalt or coal tar or phenolic resin or epoxy resin.

[0012] Preferably, the mass ratio of the lithium polyacrylate to the conductive material is (1-3):(0.1-0.5); and / or the mass ratio of the binder, the lithium polyacrylate and the conductive material is (2-3):(1-3):(0.1-0.5).

[0013] Preferably, the silicon-carbon particles include a porous carbon matrix and nano-silicon particles deposited inside the porous carbon matrix.

[0014] Preferably, the pore volume of the porous carbon matrix is ​​0.5 to 0.9 g / cm3.

[0015] Preferably, the pores of the porous carbon matrix include micropores, mesopores and macropores, and the distribution ratio of the micropores, mesopores and macropores is (88-94%): (3-6%): (3-6%).

[0016] In addition, the present invention also provides a method for preparing the negative electrode composite material.

[0017] S1, carbonizing the raw materials to form a carbon source;

[0018] S2, mixing the carbon source and the pore-forming agent, soaking and drying to form a porous carbon matrix;

[0019] S3, acid-washing, water-washing and calcining the porous carbon substrate to obtain a purified porous carbon substrate;

[0020] S4, depositing nano-silicon on the purified porous carbon matrix to obtain a porous carbon matrix on which nano-silicon is grown;

[0021] S5, mixing the product obtained in step S4 with a binder and performing a fusion treatment to form a secondary particle product;

[0022] S6. Use a functional coating material to coat the secondary particle product to obtain the negative electrode composite material.

[0023] Preferably, in step S2, the carbon source and the pore-forming agent are mixed and then soaked at room temperature for 23 to 25 hours, and dried in a forced air drying oven at 100 to 110° C. for 5 to 7 hours.

[0024] Preferably: in step S4, the deposition reaction temperature is 350° C. to 450° C., and the time is 5 h to 7 h.

[0025] Preferably, in step S5, the temperature of the fusion treatment is 200°C to 400°C.

[0026] Preferably: in step S6, the coating treatment specifically includes: mixing and dispersing lithium polyacrylate, conductive material and secondary particle product in an aqueous solvent to form a mixed slurry, and spray drying the mixed slurry under a protective atmosphere.

[0027] In addition, the present invention also provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer coated on the current collector, wherein the negative electrode active material layer comprises the negative electrode composite material according to any one of claims 10 to 14 above.

[0028] In addition, the present invention also provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer coated on the current collector, wherein the negative electrode active material layer comprises the negative electrode composite material described above.

[0029] In addition, the present invention also provides a secondary battery, including a battery cell and an electrolyte formed by sequentially stacking or winding a positive electrode sheet, a separator and a negative electrode sheet, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.

[0030] The beneficial effect of the present invention is that the negative electrode composite material provided by the present invention alleviates particle expansion and crushing through the coating effect of lithium polyacrylate, and the coating effect of lithium polyacrylate and conductive material can reduce the contact between silicon and electrolyte during the use of the negative electrode composite material, and can reduce the internal resistance of the material; thereby, the expansion of the gaps between secondary particles can be effectively alleviated, and the crushing of particles due to excessive expansion can be avoided, thereby achieving a perfect composite of carbon and silicon, and enhancing the cyclic stability of the material, greatly reducing the expansion rate of deposited silicon carbon and reducing the internal resistance of the material, thereby improving the safety of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the structure of a negative electrode composite material according to an embodiment of the present invention;

[0032] Figure 2 The figure is a flow chart of a method for preparing a negative electrode composite material according to an embodiment of the present invention.

[0033] In the figure: 1-core; 2-functional coating layer; 21-lithium polyacrylate; 22-conductive material. DETAILED DESCRIPTION

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0035] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0037] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and multiple situations exist alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0038] The following is combined with Figure 1-2 The present invention is further described in detail, but is not intended to limit the present invention.

[0039] According to a first aspect of the present invention, Figure 1 As shown, a negative electrode composite material is provided, including a core 1 and a functional coating layer 2 coated on the outer surface of the core 1, wherein the core 1 includes silicon-carbon particles; all adjacent silicon-carbon particles adhere to each other to form secondary particles; the functional coating layer 2 includes polyacrylate lithium (PAA-Li) 21 and a conductive material 22.

[0040] The negative electrode composite material of the present invention alleviates particle expansion and breakage through the adhesion effect of lithium polyacrylate, and combined with the coating effect of lithium polyacrylate and conductive material, it can reduce the contact between silicon and electrolyte in the use of the negative electrode composite material, and can reduce the internal resistance of the material; thereby, it can effectively alleviate the expansion of gaps between secondary particles, avoid particles from breaking due to excessive expansion, and then achieve a perfect composite of carbon and silicon, and enhance the cyclic stability of the material, greatly reduce the expansion rate of deposited silicon carbon and reduce the internal resistance of the material, and improve the safety of use.

[0041] In some embodiments, the conductive material is at least one of carbon nanotubes, carbon nanofibers, graphene, and conductive polymers. The conductive material is preferably single-walled carbon nanotubes (SWCNTs); at least one of carbon nanotubes, carbon nanofibers, graphene, and conductive polymers can effectively reduce the contact between silicon and electrolyte and reduce the internal resistance of the material; thereby ensuring the integrity of the entire structure and improving the cycle stability of the battery cell during the cycle.

[0042] In some embodiments, the core further includes a binder, and the silicon-carbon particles are connected by the binder to form secondary particles with micron-level or larger pores. Preferably, the binder is asphalt or coal tar or phenolic resin or epoxy resin; more preferably asphalt; the mixed bonding effect of asphalt can effectively control the particle size of nano-silicon, thereby facilitating the improvement of the performance of the negative electrode composite material.

[0043] In some embodiments, the particle size DV50 of the secondary particles is 11 to 15 μm; for example, it can be 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc. When the particle size of the secondary particles is too large, the material will expand and easily generate inert silicon carbide, and lose active silicon, and the dynamic performance will be poor. When the particle size of the secondary particles is too small, micron-level pores between the particles are difficult to form.

[0044] In some embodiments, the mass ratio of the lithium polyacrylate to the conductive material is (1-3): (0.1-0.5); for example, it can be 2:0.3, 1:0.3, 3:0.3, 1:0.1, 1:0.5, 3:0.1, 3:0.5, etc. The structure can better reduce the contact between silicon and electrolyte through the appropriate mass ratio of lithium polyacrylate and conductive material; and reasonably reduce the internal resistance of the material; and ensure the stability and safety of its use.

[0045] In some embodiments, the mass ratio of the binder, lithium polyacrylate and conductive material is (2-3): (1-3): (0.1-0.5). More lithium polyacrylate in this structure is beneficial to suppress expansion, and more conductive material is beneficial to eliminate polarization; however, more lithium polyacrylate and conductive material will affect the conductivity of the material and reduce the material capacity. In addition, if the amount of binder is small, it will affect the firmness of the overall structure, and if the amount is large, it will affect the conductivity of the material and reduce the material capacity.

[0046] In some embodiments, the silicon carbon particles include a porous carbon matrix and nano-silicon particles deposited inside the porous carbon matrix.

[0047] In some embodiments, the pore volume of the porous carbon matrix is ​​0.5 to 0.9 g / cm 3 ; For example, it can be 0.5g / cm3, 0.6g / cm3, 0.7g / cm3, 0.8g / cm3, 0.9g / cm3, etc.; The pores of the porous carbon matrix include micropores, mesopores and macropores, and the distribution ratio of the micropores, mesopores and macropores is (88-94%): (3-6%): (3-6%); For example, it can be 90%: 5%: 5%, 92%: 4%: 4% or 94%: 3%: 3%, etc. This structure can effectively ensure the stability of the assembly between the silicon-carbon particles and the lithium polyacrylate and the conductive material, and ensure the performance of the material in battery applications.

[0048] According to a second aspect of the present invention, Figure 2 As shown, the present invention also provides a method for preparing the negative electrode composite material, comprising the following steps:

[0049] S1. Heating and carbonizing the raw materials to form a carbon source; wherein the raw materials are one or more of biomass-based, resin-based, petroleum coke and anthracite;

[0050] S2, mixing the carbon source and the pore-forming agent, soaking and drying to form a porous carbon matrix;

[0051] S3, washing the porous carbon substrate with acid, washing with water until it is neutral, drying, and calcining to obtain a purified porous carbon substrate;

[0052] S4, placing the purified porous carbon matrix in a rotary kiln or a fluidized bed, introducing a mixed gas to deposit nano-silicon inside the porous carbon matrix, and obtaining a porous carbon matrix with grown nano-silicon;

[0053] S5, mixing the product obtained in step S4 with a binder and performing a fusion treatment to form a secondary particle product;

[0054] S6. Use a functional coating material to coat the secondary particle product to obtain the negative electrode composite material.

[0055] The technical solution of the present invention first performs activation, pore-forming and purification pretreatment on the carbon source after carbonization treatment, so as to obtain an intermediate product with less heteroatoms, thereby improving the performance of the material in battery applications; then, the intermediate product is deposited to obtain a porous carbon matrix, and the porous carbon matrix is ​​subjected to secondary granulation treatment, thereby effectively alleviating the expansion of the gaps between the secondary particles and avoiding the breakage of the particles due to excessive expansion; then, the secondary particle product is coated with a functional coating material to alleviate the particle expansion and breakage, reduce the contact between silicon and electrolyte, and reduce the internal resistance of the material; thereby achieving a perfect composite of carbon and silicon, enhancing the cyclic stability of the material, greatly reducing the expansion rate of the deposited silicon carbon and reducing the internal resistance of the material; and improving the safety of use.

[0056] In some embodiments, in step S1, the preset temperature for heating carbonization is 500°C to 700°C; the preset time for heating carbonization is 3h to 6h. Further, the raw material is carbonized under the conditions of a preset temperature of 500°C to 700°C and a preset time of 3h to 6h to generate the carbon source. In other words, the raw material is carbonized under a higher temperature (500°C to 700°C; wherein less than 500°C is a lower temperature; greater than 700°C is a higher temperature) and a longer time (3h to 6h; wherein less than 3h is a shorter time; greater than 6h is a longer time), while reducing heteroatoms and enhancing the stability of the formed carbon structure, providing a stable structure for subsequent pore formation and porous carbon structure production.

[0057] In some embodiments, the pore-forming agent is at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide; the mass ratio of the carbon source to the pore-forming agent is 1:1 to 1:3. This method can generate a porous carbon matrix with stronger structural stability through a reasonable proportion and a suitable type of pore-forming agent.

[0058] In some embodiments, in step S2, the carbon source and the pore-forming agent are mixed and soaked at room temperature for 23 to 25 hours, and dried in a 100 to 110°C forced air drying oven for 5 to 7 hours. Further, the carbon source and the pore-forming agent are mixed at a mixing mass ratio of 1:1 to 1:3; soaked at room temperature of 18°C ​​to 25°C for 23 to 25 hours; dried in a 100 to 110°C forced air drying oven for 5 to 7 hours; thereby increasing the concentration of strong alkali and the corrosion time compared to the current existing technology; and then obtaining a pore volume of 0.5g / cm3 to 0.9g / cm3, micropores of 88% to 94% (preferably 90%), mesopores of 3% to 6% (preferably 5%), and macropores of 3%. ~6% (preferably 5%) pore distribution structure; thereby forming a relatively large proportion of micropores and reducing the proportion of mesopores and macropores, which can avoid excessive coverage of areas with low stress points in the porous carbon matrix, thereby ensuring the structural stability of the porous carbon matrix. In addition, 5% of mesopores, 5% of macropores and 90% of micropores can ensure the fusion amount of the asphalt powder binder when the subsequent porous carbon matrix is ​​assembled with the asphalt powder binder; thereby providing a stable structure for subsequent production and ensuring the smoothness and quality of processing.

[0059] In some embodiments, in step S3, the porous carbon matrix is ​​pickled; wherein the pickling material is hydrochloric acid or the like; the product after pickling is washed with water so that the pH value of the product after pickling reaches 6.5 to 7.5; further, 0.5 to 1 mol / L hydrochloric acid is used for pickling for 30 to 50 minutes and then washed with water so that the pH value of the product reaches 7; the product with a pH value of 6.5 to 7.5 is dried to form a purified porous carbon matrix. In other words, since more impurities are generated during the pore-forming process, the product on its surface is purified by the pickling material, and the excess residual alkaline material in the alkaline washing process is neutralized, thereby effectively purifying the carbon matrix, reducing heteroatoms (especially the content of oxygen atoms), and thus improving the performance of the material in battery applications.

[0060] In some embodiments, in step S4, the mixed gas is a mixture of a protective gas and a silicon source gas; wherein the protective gas is argon, helium or nitrogen; the deposition reaction temperature is 350°C to 450°C, and the time is 5h to 7h. Further, the purified porous carbon matrix is ​​placed in a rotary kiln or a fluidized bed; a gas with a carrier gas function is introduced into the rotary kiln or the fluidized bed; wherein the gas with a fluidization function is nitrogen; the mixed gas is mixed with the fluidized product under the conditions of a deposition reaction temperature of 350°C to 450°C and a deposition reaction time of 5h to 7h to obtain a porous carbon matrix with grown nano-silicon, thereby achieving reduction to nano-silicon in the porous carbon of the second product; and nano-silicon grows in the porous carbon; and thus a porous carbon matrix with a more stable structure can be obtained.

[0061] In some embodiments, in step S5, the temperature of the fusion treatment is 200°C to 400°C (wherein 200°C to 400°C is medium temperature, greater than 400°C is high temperature; less than 200°C is low temperature). Further, the porous carbon matrix and the binder of the asphalt powder are mixed and stirred for 20min to 30min; the stirred product is subjected to a fusion treatment at a fusion temperature of 200°C to 400°C to form a secondary particle product. Therefore, multiple sedimentary silicon-carbon particles can be adhered together to form a small whole, so that the gaps between the secondary particle products can alleviate expansion, thereby improving the stability of the structure. When the fusion temperature is too low, the porous carbon matrix has more surface functional groups, resulting in low performance; when the fusion temperature is too high, the nano-silicon particle size will increase; however, the material expands greatly and is prone to generate inert silicon carbide, thereby losing active silicon and having poor dynamic performance. The medium-temperature asphalt fusion temperature is moderate, which will neither reduce the performance of the material nor generate silicon carbide. When the amount of asphalt powder is too large, the performance of the material is reduced; when the amount of asphalt powder is too small, secondary particles are difficult to form, and micron-level pores between particles are difficult to form.

[0062] In some embodiments, in step S6, the coating treatment specifically includes: mixing and dispersing lithium polyacrylate, conductive material and secondary particle product in an aqueous solvent to form a mixed slurry, and spray drying the mixed slurry under a protective atmosphere. Further, the secondary particle product is mixed and dispersed in an aqueous solvent, and then PAA-Li and SWCNT are successively put into a stirring tank with an aqueous solvent containing the secondary particle product, and the speed of the stirring tank is controlled to be 1500r / min for stirring for 2 hours to form a mixed aqueous solution. Next, the silicon-carbon material is mixed into the mixed aqueous solution, and the speed of the stirring tank at this time is 800r / min, and stirring is performed for 1 hour to form a mixed slurry; finally, the mixed slurry is spray dried under a nitrogen atmosphere; thereby, the particle expansion and crushing can be alleviated by the adhesion of PAA-Li, and the coating of PAA-Li and SWCNT reduces the contact between silicon and the electrolyte, and reduces the internal resistance of the material; in addition, the integrity of the entire structure can be ensured during the cycle and the cycle stability of the battery cell can be improved. Moreover, when the amount of PAA-Li is too much, the kinetic properties of the material will be reduced. When the amount of PAA-Li is too small, the expansion cannot be effectively alleviated. When the amount of SWCNT is too large, the ion migration impedance of the material will increase. When the amount of SWCNT is too small, the conductivity of the material will decrease and the rate performance will be reduced.

[0063] According to a third aspect of the present invention, the present invention further provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer coated on the current collector, wherein the negative electrode active material layer comprises the above-mentioned negative electrode composite material.

[0064] According to a fourth aspect of the present invention, the present invention further provides a secondary battery, comprising a battery cell formed by stacking or winding a positive electrode sheet, a separator and a negative electrode sheet in sequence, and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet mentioned above.

[0065] Example 1

[0066] Preparation of negative electrode composite materials:

[0067] 1. Carrying out carbonization treatment on anthracite at a preset temperature of 600° C. and a preset time of 5 hours to generate the carbon source;

[0068] 2. Mix the carbon source and the sodium hydroxide at a mixing mass ratio of 1:1; soak at room temperature 25° C. for 24 hours; and dry in a blast drying oven at 105° C. for 6 hours to form a porous carbon matrix;

[0069] 3. The porous carbon matrix is ​​pickled with hydrochloric acid; the pore-forming product is washed with 0.5 mol / L hydrochloric acid for 30 min to make the pH value of the pore-forming product reach 7; the product with a pH value of 7 is dried to form a purified porous carbon matrix;

[0070] 4. Placing the purified porous carbon matrix in a rotary kiln or a fluidized bed; introducing carrier gas nitrogen into the rotary kiln or the fluidized bed; mixing the mixed gas with the fluidized product under the conditions of a deposition reaction temperature of 450° C. and a deposition reaction time of 6 h to obtain a porous carbon matrix for growing nano-silicon;

[0071] 5. The porous carbon matrix and the asphalt powder were mixed and stirred for 25 minutes; the stirred product was subjected to a fusion treatment at a fusion temperature of 400°C to form a secondary particle product; wherein the amount of medium-temperature asphalt used was 3%; the particle size D of the obtained secondary particle product V 50 is 13 μm;

[0072] 6. The secondary particle product, lithium polyacrylate (PAA-Li) and single-walled carbon nanotubes (SWCNT) are mixed and dispersed in an aqueous solvent to prepare a mixed slurry; specifically, PAA-Li and SWCNT are successively put into a stirring tank, wherein the mass content of PAA-Li used is 2%, and the mass content of SWCNT used is 0.3%, and the speed of the stirring tank is controlled to 1500r / min for stirring for 2 hours; then, the secondary particle product is added, and the speed of the stirring tank is controlled to 800r / min for stirring for 1 hour to form a mixed slurry; finally, the mixed slurry is spray-dried under a nitrogen atmosphere to obtain a negative electrode composite material.

[0073] After testing, the expansion rate of the negative electrode composite material obtained in this embodiment is 60%, and the capacity (1.5V, mAh / g) is 1800; the performance of the negative electrode composite material (1.5v,%) is 91%; the capacity retention rate of the negative electrode composite material at 500mAh / g blending gram-capacity cycle (1C / 1C, 500cls) is 88%.

[0074] Preparation of negative electrode:

[0075] The negative electrode composite material, conductive agent (carbon nanotubes) and binder (PAA) prepared above were mixed in a mass ratio of 98:1:1 to prepare a negative electrode slurry, the negative electrode slurry was coated on the current collector copper foil, dried at 85°C and then cold pressed, and then trimmed, cut and stripped, and then dried at 85°C under vacuum conditions, and the copper-nickel-plated tabs were welded to prepare a negative electrode sheet.

[0076] Preparation of lithium-ion batteries:

[0077] The negative electrode sheet, separator (PP), and positive electrode sheet (nickel cobalt manganese oxide positive electrode) prepared above are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic film outer package, and the prepared electrolyte is injected into the dried battery, and the battery is packaged, allowed to stand, formed, shaped, and capacity divided to complete the preparation of the lithium-ion battery.

[0078] Example 2

[0079] The only difference between Example 2 and Example 1 is that the amount of high-temperature asphalt used is 3%.

[0080] Example 3

[0081] The only difference between Example 3 and Example 1 is that the amount of low-temperature asphalt used is 3%.

[0082] Example 4

[0083] The only difference between Example 4 and Example 1 is that the amount of PAA-Li is 1%.

[0084] Example 5

[0085] The only difference between Example 5 and Example 1 is that the amount of PAA-Li is 3%.

[0086] Example 6

[0087] The only difference between Example 6 and Example 4 is that the amount of SWCNT is 0.1%.

[0088] Example 7

[0089] The only difference between Example 7 and Example 4 is that the amount of SWCNT is 0.5%.

[0090] Example 8

[0091] Example 8 The only difference between Example 8 and Example 1 is that the particle size DV50 of the obtained secondary particle product is 11.

[0092] Example 9

[0093] The difference between Example 9 and Example 1 is that the particle size D of the secondary particle product obtained is V 50 is 15.

[0094] Comparative Example 1

[0095] The difference between Comparative Example 1 and Example 1 is that PAA-Li, SWCNT and asphalt are not used; and the particle size D of the secondary particle product is V 50 is 8.5.

[0096] Comparative Example 2

[0097] The difference between Comparative Example 2 and Comparative Example 1 is that the amount of PAA-Li used is 2%, SWCNT and asphalt are not used, and the particle size D of the secondary particle product is V 50 is 8.5μm.

[0098] Comparative Example 3

[0099] The difference between Comparative Example 3 and Example 1 is that the amount of SWCNT used is 0.3%, PAA-Li and asphalt are not used, and the particle size D of the secondary particle product is V 50 is 8.5μm.

[0100] Comparative Example 4

[0101] The difference between Comparative Example 4 and Example 1 is that the amount of medium-temperature asphalt used is 3%, SWCNT and PAA-Li are not used, and the particle size D of the secondary particle product is V 50 is 13μm.

[0102] Comparative Example 5

[0103] The difference between this comparative example 5 and example 1 is that: no asphalt is used; the amount of PAA-Li used is 2%; the amount of SWCNT used is 0.3%; and the particle size D of the secondary particle product is V 50 is 13μm.

[0104] Comparative Example 6

[0105] The difference between this comparative example 6 and the example 1 is that: SWCNT is not used; the amount of PAA-Li used is 2%; the amount of asphalt used is 3%; and the particle size D of the secondary particle product is V 50 is 13μm.

[0106] Comparative Example 7

[0107] The only differences between Comparative Example 7 and Example 1 are that: PAA-Li is not used; the amount of SWCNT used is 0.3%; the amount of asphalt used is 3%; and the particle size DV50 of the secondary particle product is 13 μm.

[0108] Comparative Example 8

[0109] The only difference between Comparative Example 7 and Example 1 is that the particle size DV50 of the secondary particle product is 17 μm.

[0110] Electrochemical performance tests were performed on the negative electrode sheets and lithium-ion batteries prepared in the above embodiments and comparative examples, respectively. The test results are shown in Tables 1-2.

[0111] Table 1

[0112]

[0113] Table 2

[0114]

[0115]

[0116] From the test results in Table 1 and Table 2 above, we can see that:

[0117] 1. Compared with Comparative Example 4, Example 1 shows a 40% reduction in expansion. This is attributed to the fact that if only secondary granulation is performed, the silicon-carbon material will expand greatly during the cycle. In addition, in the later cycle, the asphalt bonding force becomes weaker and weaker, and it becomes a single particle again. However, in this solution, lithium polyacrylate and conductive materials are coated during secondary granulation to maintain the integrity of the secondary particles. The lithium acrylate is flexible and can stretch along with the particles when the silicon expands, effectively preventing the silicon particles from contacting the electrolyte. Therefore, the secondary granulation and the coating of lithium polyacrylate and conductive materials in this solution work together as a whole to better inhibit expansion.

[0118] 2. Due to expansion, both capacity and expansion are taken into consideration, and expansion is more important. Therefore, when preparing the negative electrode composite material, the optimal amount of PAA-Li used in production is 2%, the optimal amount of SWCNT is 0.3%, and the optimal amount of medium-temperature asphalt is 3%. The optimal value of the particle size DV50 of the secondary particle product obtained is 13. Thus, the expansion rate of the obtained negative electrode composite material is 60%, and the capacity (1.5V, mAh / g) is 1800. The capacity retention rate of the 500mAh / g blended gram-capacity cycle (1C / 1C, 500cls) of the negative electrode composite material is 88%.

[0119] 3. When preparing negative electrode composite materials, if the temperature of the asphalt is too low, there will be more surface functional groups, which will affect the ease of assembly between them; if the temperature of the asphalt is too high, the nano-silicon particle size will increase, the material will expand greatly and it will be easy to generate inert silicon carbide, lose active silicon, and have poor kinetic performance.

[0120] 4. When preparing negative electrode composite materials, if the amount of asphalt is too large, the performance of the material will be reduced; if the amount of asphalt is too small, secondary particles are difficult to form and micron-sized pores between particles are difficult to form.

[0121] 5. When preparing negative electrode composite materials, if the amount of PAA-Li is too much, the kinetic properties of the material will be reduced; if the amount of PAA-Li is too little, the expansion cannot be effectively alleviated.

[0122] 6. When preparing negative electrode composite materials, too much SWCNT will increase the ion migration impedance of the material; too little SWCNT will reduce the conductivity of the material and reduce the rate performance.

[0123] In summary, the negative electrode composite material provided by the present invention alleviates particle expansion and breakage through the adhesion effect of lithium polyacrylate. Combined with the coating effect of lithium polyacrylate and conductive material, it can reduce the contact between silicon and electrolyte during the use of the negative electrode composite material, and can reduce the internal resistance of the material; thereby, it can effectively alleviate the expansion of gaps between secondary particles, avoid particles from breaking due to excessive expansion, and thus achieve a perfect composite of carbon and silicon, and enhance the cyclic stability of the material, greatly reduce the expansion rate of deposited silicon carbon and reduce the internal resistance of the material, thereby improving the safety of use.

[0124] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A negative electrode composite material, characterized in that: It comprises an inner core and a functional coating layer coated on the outer surface of the inner core, wherein the inner core comprises silicon-carbon particles; all adjacent silicon-carbon particles adhere to each other to form secondary particles; and the functional coating layer comprises lithium polyacrylate and a conductive material.

2. The negative electrode composite material according to claim 1, characterized in that: The conductive material is at least one of carbon nanotubes, carbon nanofibers, graphene, and conductive polymers.

3. The negative electrode composite material according to claim 1, characterized in that: The inner core further comprises a binder, and the silicon-carbon particles are connected by the binder to form the secondary particles having pores of micrometer level or above.

4. The negative electrode composite material according to claim 3, characterized in that: The particle size DV50 of the secondary particles is 11 to 15 μm.

5. The negative electrode composite material according to claim 3, characterized in that: The binder is asphalt or coal tar or phenolic resin or epoxy resin.

6. The negative electrode composite material according to claim 1, characterized in that: The mass ratio of the lithium polyacrylate to the conductive material is (1-3): (0.1-0.5); and / or the mass ratio of the binder, the lithium polyacrylate and the conductive material is (2-3): (1-3): (0.1-0.5).

7. The negative electrode composite material according to claim 1, characterized in that: The silicon-carbon particles include a porous carbon matrix and nano-silicon particles deposited inside the porous carbon matrix.

8. The negative electrode composite material according to claim 7, characterized in that: The pore volume of the porous carbon matrix is ​​0.5 to 0.9 g / cm3.

9. The negative electrode composite material according to claim 7, characterized in that: The pores of the porous carbon matrix include micropores, mesopores and macropores, and the distribution ratio of the micropores, mesopores and macropores is (88-94%): (3-6%): (3-6%).

10. A method for preparing the negative electrode composite material according to any one of claims 1 to 9, characterized in that: Includes the following: S1, carbonizing the raw materials to form a carbon source; S2, mixing the carbon source and the pore-forming agent, soaking and drying to form a porous carbon matrix; S3, acid-washing, water-washing and calcining the porous carbon substrate to obtain a purified porous carbon substrate; S4, depositing nano-silicon on the purified porous carbon matrix to obtain a porous carbon matrix on which nano-silicon is grown; S5, mixing the product obtained in step S4 with a binder and performing a fusion treatment to form a secondary particle product; S6. Use a functional coating material to coat the secondary particle product to obtain the negative electrode composite material.

11. The method for preparing the negative electrode composite material according to claim 10, characterized in that: In step S2, the carbon source and the pore-forming agent are mixed and soaked at room temperature for 23 to 25 hours, and dried in a forced air drying oven at 100 to 110° C. for 5 to 7 hours.

12. The method for preparing the negative electrode composite material according to claim 10, characterized in that: In step S4, the deposition reaction temperature is 350° C. to 450° C., and the time is 5 h to 7 h.

13. The method for preparing the negative electrode composite material according to claim 10, characterized in that: In step S5, the temperature of the fusion treatment is 200°C to 400°C.

14. The method for preparing the negative electrode composite material according to claim 10, characterized in that: In step S6, the coating treatment specifically includes: mixing and dispersing lithium polyacrylate, conductive material and secondary particle product in an aqueous solvent to form a mixed slurry, and spray drying the mixed slurry under a protective atmosphere.

15. A negative electrode sheet, characterized in that: The invention comprises a current collector and a negative electrode active material layer coated on the current collector, wherein the negative electrode active material layer comprises the negative electrode composite material according to any one of claims 10 to 14.

16. A secondary battery, characterized in that: It comprises a battery cell and an electrolyte formed by stacking or winding a positive electrode sheet, a separator and a negative electrode sheet in sequence, wherein the negative electrode sheet is the negative electrode sheet as claimed in claim 15.

Citation Information

Cited By

  • Battery monomer and preparation method thereof, battery device and power utilization device

    CN121601664A